Acute Necrotizing Pancreatitis following Long-Term Antipsychotic Use. (31st August 2021) - Liebers, David T.; Ofomata, Adaora; Badolato, Ryan; Mills, Emily; Farahmand, Pantea
Abstract : Introduction . Psychiatrists commonly use antipsychotic medications in the treatment of psychotic and mood disorders. A rare but known side effect of atypical antipsychotics is acute pancreatitis. Most cases of antipsychotic-induced pancreatitis occur within six months of initiation. The mechanism believed to cause this reaction is hypertriglyceridemia. Here, we present a unique case of antipsychotic-induced pancreatitis that deviates from previous cases in the time to onset of the pancreatitis and the mechanism of presentation. Case Presentation . We present a case of a patient with treatment-resistant schizophrenia managed for over a decade on olanzapine and haloperidol. Twelve years after stabilization on this medication regimen, the patient developed acute pancreatitis, which after extensive medical workup was attributed to his psychotropic medications. We review his medical and psychiatric history, his medical course and workup during the episode of pancreatitis, and review recommendations for patients at risk for antipsychotic-induced pancreatitis based on this case and the current literature. Discussion . This case illustrates that acute pancreatitis can occur long after the initiation of antipsychotic medications and may be mediated by mechanisms other than hypertriglyceridemia. While there are reports of antipsychotic-induced psychosis occurring within months, and in a limited set of cases, years, after medication initiation, the twelve-year time interval in the present case is by far the longest duration of an antipsychotic precipitating this adverse event recorded in the literature. This case highlights that although exceedingly rare, prescribers should be aware of the risk for drug-induced pancreatitis in patients stable on antipsychotic medications.